Functional and rheological investigations on hydrophilic nanoclay blended bitumen - Hazratullah Paktin; M. Kumar; V. Vinayaka Ram; Siksha Swaroopa Kar (Discover Sustainability, 2024)
Abstract Functional and rheological characteristics are two essential criteria for the success of any modifiers for the modification of bitumen. Recently, nanoclay has grabbed extensive attention as a key solution for enhancing the performance of bitumen. This study focuses on evaluating the dispersion, storage stability, high-temperature performance, and aging resistance potential properties of bitumen VG-30 modified with montmorillonite bentonite hydrophilic nanoclay (NC). Various proportions (0, 2, 4, 6, and 8% by weight of bitumen) of NC were blended with VG-30 using a high shear mixer (HSM). Various performance assessments, including kinematic viscosity by Brookfield Rotational Viscometer (BRV), multiple stress creep recovery (MSCR), high-temperature performance grade (PG), frequency sweep along with scanning electron microscopy (SEM) were conducted. SEM images and viscosity data analysis show that dispersion problem arises beyond 6% of NC addition while phase separation is in the acceptable range. Further, considerable increment in Superpave rutting parameter (G*/Sinδ) and recovery percentage (%R), and decrease in non-recoverable compliance (Jnr) was seen, resulted up to 30% improvement in rutting performance of the bitumen. Furthermore, the potential for aging resistivity resulted a significant drop in aging index (AI) values, suggesting that introducing NC to bitumen could significantly improve aging resistivity. Moreover, rheological approaches can be helpful to understand temperatures and frequency dependent aging behaviours of bitumen.